Application of effluent reduction methods and treatment using advanced oxidation process at leather chemicals and tanning industries - Ali, Azhar; Shaikh, Irfan Ahmed; Ahmad, Sajid Rashid; Shakoor, Muhammad Bilal; Yong, Jean Wan Hong; Rizwan, Muhammad; Samina, Faiza (Frontiers in Environmental Science, 2024)
The current study set out to assess and create long-term solutions for improving environmental performance concerning water use, wastewater production, and treatment at Syntan plant (glasslined vessel unit) and application laboratory (small-scale leather retanning. Based on evaluations and analyses, best available techniques including water gauging, pressurized vessel washing, dedication of vessels to similar production, reuse techniques, developing commercial grade intermediate products from wash water, managing cooling water and developing reuse methods of reverse osmosis reject water were applied to reduce water consumption and effluent generation in process and non-process activities. Furthermore, the reduced effluent was subjected to treat using electrochemical processes i.e., electrocoagulation and electro-Fenton, before it was drained to outside environment. As a result of the applications, 0 to 100 % change was measured in various process and non-process activities, whereas, 12.8% to 100% reduction was measured in effluent.Soft cooling water consumption was reduced by 46.7%. The results of treated effluent parameters were compared and found the final removal efficiencies of total dissolved solids (TDS) (51.4%), total suspended solids (TSS) (99.2%), chemical oxygen demand (COD) (98.5%) and electric conductivity (67.7%). It is concluded that this study can be considered as a successful model to increased water efficiency in chemical industries, Furthermore, it could serve as a building block for the incorporation of cleaner and sustainable production approach into national agenda and to overcome stern issues of high-water and energy consumption and effluent management in different industries.